2014
DOI: 10.1155/2014/924296
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Air Exposure Elicits an Intestinal Inflammation Resulting in Postoperative Ileus

Abstract: Background. The pathogenesis of postoperative ileus (POI) is complex. The present study was designed to investigate the effects of peritoneal air exposure on the POI intestinal inflammation and the underlying mechanism. Methods. Sprague-Dawley rats were randomized into five groups (6/group): the control group, the sham group, and three exposure groups with peritoneal air exposure for 1, 2, or 3 h. At 24 h after surgery, we analyzed the gastrointestinal transit, the serum levels of tumor necrosis factor (TNF)-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…In the previous study, charcoal transport is commonly used as an objective measurement to assess gastrointestinal motility in animal research. 23,30,35,36) These studies demonstrate that POI is associated with decreased gastrointestinal transit assessed by charcoal transport. In the present study, we also employed charcoal transport to determine the gastrointestinal motility, and further investigate the improvement effect of GRb1 on POI.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In the previous study, charcoal transport is commonly used as an objective measurement to assess gastrointestinal motility in animal research. 23,30,35,36) These studies demonstrate that POI is associated with decreased gastrointestinal transit assessed by charcoal transport. In the present study, we also employed charcoal transport to determine the gastrointestinal motility, and further investigate the improvement effect of GRb1 on POI.…”
Section: Discussionmentioning
confidence: 59%
“…16,21,22) Among these factors, accumulating evidence indicates that intestinal inflammation plays an important role in the pathophysiology of POI. 16,23,24) The extent of intestinal manipulation during abdominal surgery causes the degree of intestinal inflammation and further determines the duration and severity of gastrointestinal dysmotility. 25) Therefore, methods to reduce intestinal inflammation and shorten postoperative rehabilitation course are popular pursuits in modern surgery.…”
Section: Anti-inflammatory Effect Of Ginsenoside Rb1 Contributes To Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important lipid peroxidation production in the oxidative stress process, an MDA increase may indicate the increased oxidative stress injury followed by uremia. 25) SOD, one of the main antioxidant enzymes, could prevent the body from oxidative stress injury. 38) In the present study, berberine treatment was shown to significantly increase the intestinal SOD activity, compared with the uremic group.…”
Section: Discussionmentioning
confidence: 99%
“…The MPO activity (units/g tissue) was quantitatively measured by spectrophotometry at 460 nm as described in our previous study. 25) Histopathological Analysis The removed terminal ileum was fixed with 10% buffered formaldehyde solution and embedded in paraffin. Slices of 4-µm thickness were made, and stained with hematoxylin and eosin (H&E).…”
Section: )mentioning
confidence: 99%